Combined Effect of Nano Ferrite and Nano Silica on Properties of Cement Mortar - K. Salman, Ghaed; R. Rawdhan, Rasha; J. Bohan, Azhar; Al-Jubouri, Muhanad (International Journal of Integrated Engineering, 2024)
This study investigates the effects of adding nano-ferrite (N.F.) and nano-silica (N.S.) on the mechanical and biological properties of mortar. By assessing four water-to-cement ratios (1-4%), the ideal nanoparticle doses were determined. Results indicated that both N.F. and N.S. significantly increased the mortar's strength at ratios between 1% and 4%, while combinations of N.F. and N.S. improved strength up to 3% and 4% substitution, respectively. The mechanisms of strength enhancement were attributed to nanoparticles acting as fillers and hydration accelerators, which densify the mortar microstructure and promote the production of calcium silicate hydrate (C-S-H) gels. In terms of biological properties, the study examined the antibacterial effects of nano-silica and nano-ferrite. Nano-silica demonstrated greater antibacterial potency against all bacterial strains assessed. Both materials exhibited a stronger antibacterial impact on Gram-positive bacteria (Staphylococcus aureus) compared to Gram-negative bacteria (Escherichia coli), due to differences in cell wall structures. The study emphasizes the importance of optimal nanoparticle dosages and identifies limitations that warrant further research, such as durability and potential downsides at higher concentrations. Despite these challenges, the findings underscore the potential of nanoparticles to enhance mortar performance and suggest promising applications in construction and the development of antibacterial materials. Future research should focus on overcoming these constraints and exploring the practical applications of nanoparticle-enhanced mortar in real-world scenarios.